UTILIZING DIGITAL MEDIA IN EFL CLASSROOM: PRE-SERVICE TEACHERS TEACHING PRACTICE EXPERIENCE - Wiwik Mardiana (Universitas Lambung Mangkurat, 2020)
The emergence of digital media in this decade becomes a trend in teaching English since millennial generations are considered as active users of technology. For this reason, this study aims at investigating the pre-service teachers’ perspective toward the use of digital media in EFL classrooms based on their teaching practice experience. The participants were twenty students of Universitas Islam Majapahit who did a school-based field study program. The researcher gained the data through an opened-ended questionnaire and analyzed qualitatively. The results indicate that digital media is beneficial for both the pre-service teachers and the students. The pre-service teachers' view on the influence of digital media on students’ attitudes and proficiency and the pre-service teachers’ obstacles is further discussed.